DETERMINANTS OF PUBLIC DECISION-MAKING IN SELECTING SUBSIDIZED HOME FINANCING AT ISLAMIC BANKS - M. Tegar Pratama; Armansyah Walian; Aryanti; Listiawati (CV. Cendekiawan Muda Sriwijaya, 2025)
This study aims to identify the factors that influence people's decisions in applying for subsidized mortgage financing (KPR Subsidy) at Islamic banks, with a case study focus on Bank Syariah Indonesia (BSI). The research population includes all customers who have taken out a KPR Subsidy at the BSI Palembang Branch Office. The sampling technique used is non-probability sampling, specifically the accidental sampling method, which involves selecting respondents based on chance encounters between the researcher and members of the population who are willing to participate. A total of 100 BSI KPR Subsidy customers were selected as the sample. For data processing, this study utilizes SPSS version 20 and employs multiple linear regression analysis. This method is applied to examine the influence of several independent variables simultaneously on a single dependent variable. The results show that the housing location factor has a positive and significant effect on customers’ decisions to apply for a KPR Subsidy, with a t-value of 5.666, which is greater than the t-table value of 1.985, and a significance level of 0.000, which is below the 0.05 threshold. Furthermore, the housing price also has a positive and significant effect, with a t-value of 4.220 > t-table 1.985 and a significance level of 0.000 < 0.05. Similarly, the promotion factor shows a positive and significant influence on the decision to take the KPR Subsidy, with a t-value of 4.806 > t-table 1.985 and a significance level of 0.000 < 0.05.